2020
DOI: 10.1080/09687637.2020.1852180
|View full text |Cite
|
Sign up to set email alerts
|

Gender and recovery pathways in the UK

Abstract: She has a broad range of research interests including addiction and recovery, violence, gambling and comparative studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 52 publications
2
20
1
Order By: Relevance
“…This resulted in some women discussing their discomfort in mixed gender groups, highlighting the potential for women to experience genderspecific barriers to recovery due to trauma. The growth of gender-specific and gender responsive services can therefore be encouraged in light of this (Agenda, 2017;Andersson et al, 2020;Covington, 2008;Day et al, 2018), however as noted by Neale et al (2018) and Wincup (2019) women may still benefit from mixed-gender services provided they are gender-sensitive.…”
Section: Social Network: Network Change Peer Support and Identity Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in some women discussing their discomfort in mixed gender groups, highlighting the potential for women to experience genderspecific barriers to recovery due to trauma. The growth of gender-specific and gender responsive services can therefore be encouraged in light of this (Agenda, 2017;Andersson et al, 2020;Covington, 2008;Day et al, 2018), however as noted by Neale et al (2018) and Wincup (2019) women may still benefit from mixed-gender services provided they are gender-sensitive.…”
Section: Social Network: Network Change Peer Support and Identity Formationmentioning
confidence: 99%
“…Despite what is known about differential experiences of recovery by gender, it is argued that there remains a gap between policy and practice. The latest Alcohol Strategy (HM Government, 2012) and Drug Strategy (HM Government, 2017) note the importance of supporting recovery, and whilst both strategies recognise that recovery encompasses much more than abstinence, there has been limited focus on the gendered implications of addiction and recovery to date (Andersson et al, 2020;Wincup, 2016Wincup, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…The paucity of recovery studies that focus on gender issues is addressed in this special issue, not only by the photovoice paper (Van Steenberghe et al, 2021), but also in papers by Collinson & Hall (2021), Kougiali et al (2021), and Andersson et al (2020). Based on a secondary analysis of two qualitative studies of women in recovery, Collinson and Hall (2021) describe recovery as a socially mediated process that involves different recovery mechanisms and mediators for women compared to men.…”
Section: Mechanisms and Mediators Of Addiction Recoverymentioning
confidence: 99%
“…Frequently mentioned resources were supportive social and family environments (Anderson et al, 2021;Dekkers et al, 2021;, recovery-supportive housing facilities (Jason et al, 2021), and personalised and holistic support services (Bellaert et al, 2021;Jouet et al, 2021;Van Steenberghe et al, 2021). Finally, several papers show that women face different challenges compared with men in recovery, as they experience more mental health and family needs (Andersson et al, 2020) and are more often confronted with adverse childhood experiences and multiple stigma (Kougiali et al, 2021), indicating the need for gender-sensitive recovery services (Collinson & Hall, 2021). One outstanding question is whether these observations can be extended to other gender identities not included in these studies.…”
Section: Mechanisms and Mediators Of Addiction Recoverymentioning
confidence: 99%
“…In their study of mental health recovery among people labelled as not criminally responsible, Aga et al (2021) found that connectedness is central to the recovery experience, including a sense of belonging that is linked to active engagement in social groups and society at large. Taking care of children has been identified as a major barrier to seeking treatment for women (because of concerns of involvement of social services and the perceived threat of child removal), as well as an important factor promoting treatment retention and recovery in mother-child programs (Neale et al, 2018;Andersson et al, 2020;Schamp et al, 2020), where reunification with children or retaining custody of children can be a strong motivation to strive for recovery.…”
Section: Introductionmentioning
confidence: 99%